2022
DOI: 10.1002/dta.3324
|View full text |Cite
|
Sign up to set email alerts
|

Detection of de‐N‐glycosylated EPO with SDS‐PAGE: A complementary confirmation procedure for recombinant EPO in blood samples

Abstract: Frameshift variant c.577del in the EPO gene can result in the extension of the amino acid sequence of EPO by invalidating the termination codon. As the molecular weight of its encoded protein EPO (VAR-EPO) is similar to that of rEPO, the World Anti-Doping Agency has published Annex B to the TD2022EPO in order to protect athletes with variant c.577del from the suspicion of rEPO administrations. However, it is still necessary to develop a confirmation method for rEPO that can discriminate rEPO from VAR-EPO.Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…This approach, however, has been particularly challenging in female subjects, especially when micro- suggested an alternative approach based on N-deglycosylation of serum (or plasma) EPO prior to SAR-PAGE analysis. 60 The presence of a double band with characteristic abundance ratios is indicative for a heterozygote, whereas the detection of a single band or atypical abundance ratios supports the identification of rhEPO in such specimens.…”
Section: Steroid Profiling In Urine and Bloodmentioning
confidence: 98%
See 1 more Smart Citation
“…This approach, however, has been particularly challenging in female subjects, especially when micro- suggested an alternative approach based on N-deglycosylation of serum (or plasma) EPO prior to SAR-PAGE analysis. 60 The presence of a double band with characteristic abundance ratios is indicative for a heterozygote, whereas the detection of a single band or atypical abundance ratios supports the identification of rhEPO in such specimens.…”
Section: Steroid Profiling In Urine and Bloodmentioning
confidence: 98%
“…The analytical image obtained from urine samples collected from heterozygous individuals carrying the c.577del variant is similar to those of mixed‐band scenarios, which is why the WADA technical document concerning the analysis and reporting of EPO findings was modified to account for this observation 59 . Confirmatory analyses by, for example, DNA sequencing of the EPO gene region encompassing c.577 are rarely available, which is why He et al suggested an alternative approach based on N ‐deglycosylation of serum (or plasma) EPO prior to SAR‐PAGE analysis 60 . The presence of a double band with characteristic abundance ratios is indicative for a heterozygote, whereas the detection of a single band or atypical abundance ratios supports the identification of rhEPO in such specimens.…”
Section: Peptide Hormones Growth Factors Related Substances and Mimeticsmentioning
confidence: 99%
“…We have already developed a de‐ N ‐glycosylated method that could be applied to blood samples to discriminate rEPO and VAR‐EPO in the spiked study 6 . In this project, an administration study on the c.577del variant carriers was conducted, after injection of rEPO urine and blood samples were collected, and the EPO electrophoretic pattern was obtained, for the purpose of evaluating whether de‐ N ‐glycosylation was an effective method that can reliably identify rEPO in variant carriers.…”
Section: Introductionmentioning
confidence: 99%
“…15 The analytical differentiation of natural/endogenous EPO, rhEPO, and the recently described variant (frameshift c.577del) of human EPO 16 was accomplished by Ndegylcosylation prior to gel electrophoretic analysis, with non-variant EPO and rhEPO-spiked samples yielding a single band while EPO variant-containing serum samples produced consistently two separate bands. 17 Further, in the context of blood doping, the utility of monitoring the number of circulating red blood cell extracellular vesicles was investigated in a simulated scenario of autologous blood transfusion. A significant alteration was observed when comparing pre-and post-transfusion levels; however, in consideration of the pilot study character of these results, further research was seen necessary to assess the true added value.…”
mentioning
confidence: 99%
“…Conversely, the hematological module of the ABP was shown to flag 24% of samples collected during a controlled recombinant human erythropoietin (rhEPO) microdosing event, underlining the relevance of complementary approaches in anti‐doping 15 . The analytical differentiation of natural/endogenous EPO, rhEPO, and the recently described variant (frameshift c.577del) of human EPO 16 was accomplished by N ‐degylcosylation prior to gel electrophoretic analysis, with non‐variant EPO and rhEPO‐spiked samples yielding a single band while EPO variant‐containing serum samples produced consistently two separate bands 17 . Further, in the context of blood doping, the utility of monitoring the number of circulating red blood cell extracellular vesicles was investigated in a simulated scenario of autologous blood transfusion.…”
mentioning
confidence: 99%